Pharmaceutical analysis : a textbook for pharmacy students and pharmaceutical chemists - Watson, David G. (Edinburg, New York : Elsevier, Churchill Livingstone, 2012)
The fundamental principles of obtaining reliable analytical data do not change, but some instrumental methods have changed greatly in the 12 years since the first edition- none more so than mass spectromerty.
Control of the quality of analytical methods -- Physical and chemical properties of drug molecules -- Titrimetric and chemical analysis methods -- Ultraviolet and visible spectroscopy -- Infrared spectrophotometry -- Atomic spectrophotometry -- Molecular emission spectroscopy -- Nuclear magnetic resonance spectroscopy -- Mass spectrometry -- Chromatographic theory -- Gas chromatography -- High-pressure liquid chromatography -- Thin layer chromatography -- High-performance capillary electrophoresis -- Extraction methods in pharmaceutical analysis
Includes bibliographical references and index.
Keywords: SPECTRUM ANALYSIS METHODS